CD86 Expression by Monocytes Influences an Immunomodulatory Profile in Asymptomatic Patients with Chronic Chagas Disease - Pinto, Bruna F.; Medeiros, Nayara I.; Teixeira-Carvalho, Andrea; Eloi-Santos, Silvana M.; Fontes-Cal, Tereza C. M.; Rocha, Débora A.; Dutra, Walderez O.; Correa-Oliveira, Rodrigo; Gomes, Juliana A. S. (Frontiers in Immunology, 2018)
In the chronic phase of Chagas disease, 60% of the patients develop the asymptomatic form known as indeterminate (IND). The remaining 30% of the patients develop a life-threatening form in which digestive and/or cardiac alterations take place. The mechanisms underlying the development of severe forms of Chagas disease remain poorly understood. It is well known that interactions between immune cells such as monocytes and lymphocytes drive immune responses. Further, the co-stimulatory molecules CD80 and CD86 expressed by monocytes and subsets induce lymphocyte activation, thereby triggering cellular immune response. Here we revealed, for the first time, the functional-phenotypic profile of monocytes subsets in Chagas disease. Using flow cytometry, we evaluated the effect of in vitro stimulation with Trypanosoma cruzi antigens on the expression of the co-stimulatory molecules CD80 and CD86 in different monocyte subsets of patients with IND and cardiac (CARD) clinical forms of Chagas disease. We also assessed the expression of TLR-2, TLR-4, TLR-9, HLA-DR, IL-10 and IL-12 in the monocyte subsets and of CTLA-4 and CD28, ligands of CD80 and CD86, in T lymphocytes. CD86 expression in all monocyte subsets was higher in IND patients when compared to non-infected individuals (NI). After stimulation with T. cruzi, these patients also showed a higher frequency of CD4+CTLA-4+ T lymphocytes than NI individuals. We found an association between CD80 and CD28, and between CD86 and CTLA-4 expression, with a high frequency of Treg cells in IND patients. We proposed that CD86 may be involved in immunoregulation by its association with CTLA-4 and is responsible for the activation of Treg cells in asymptomatic patients. CD86 and CTLA-4 interaction may influence Treg activation, and this could represent a new strategy to control inflammation and tissue damage.